The Pivotal Role of Quality Technical Structures for Clinical Trials Oversight in the Achievement of Long-Term Capacity Strengthening Outcomes - Owusu Sekyere, Solomon; Škrnjug-Yudov, Ivana; Pinz, Alexander; Meyer, Heidi; Conrad, Christoph (Frontiers in Medicine, 2022)
Background: Development of safe and efficacious medicines in many sub-Saharan African countries remains hampered due to fragmented health research infrastructure and ineffective regulatory oversight. To boost the latter in the area of Clinical Trials (CT) Oversight (CTO), many international programs and Regional Centers for Regulatory Excellence (RCORE) initiatives offer various trainings to help strengthen human resource capacity. We aimed at evaluating the training outcomes (at home-institution level) of sponsored fellows for one of such capacity strengthening interventions; a measure that is less often reported and thus remains poorly understood. Method: The Global Health Protection Programme’s VaccTrain project sponsored nine regulatory staff from eight National Medicines Regulatory Authorities (NMRAs) in sub-Saharan Africa for the RCORE CT Training Fellowship by FDA Ghana in a particular year. Using a systematized evaluation framework based on the theory of change, we assessed the individual- and NMRA-level achievement of pre-defined training outcomes. For this purpose, data was collected at pre-training and at short- and long-term evaluation time-points using a survey instrument. Results: At pre-training, our data revealed existence of differential expectations and orientations among the training participants, thus providing an early indication of potential distinctive patterns in achievement of desired training outcomes. In a short-term post-training follow-up evaluation, our data revealed a two-group clustering of fellows based on the achievement of training outcomes where only one group (representing 44%) reported achievement of CTO-related outcomes. At this time-point, achievement of training outcomes was associated with the vibrancy of CT activity and existence of a comprehensive technical structure for CTO. In a further long-term follow-up evaluation, our data revealed a successful achievement of CTO-related individual- and/or institutional-level outcomes in all but one fellow. Here again, availability of a robust technical structure for CTO (and perhaps fellow affiliation/selection) – but not CT vibrancy – showed a trend of temporal association with achievement of training outcomes. Conclusion: Given the pivotal role operational structures of international standards at home institutions play in translating training-acquired knowledge into measurable CTO-related outcomes, we encourage that capacity strengthening projects aimed at achieving health-related targets of Sustainable Development Goals adopt an approach built on this foundation.